Compliment responses among male and female Jordanian university students - Al-rousan, Mohammad Yahya; Norsimah Mat Awal,; Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study was conducted to examine compliment responses among Jordanian university students. It aims to explore the use of compliment responses among Jordanian, and investigate if there are any differences with regard to gender. The corpus consists of 611 compliment responses collected from 36 participants through an ethnographic (note-taking) method during the second semester of 2013/2014 academic session. This research adopted Herbert’s (1990) taxonomy of compliment response strategies to analyze the compliment responses. Results show that recipients used the agreement strategies more frequently than the other strategies. The findings also show although both males and females favored to use agreement strategies more than non agreement and other interpretation strategies, female students used agreement strategies more frequently than the male students. This may support the claim that males tend to interpret compliment as FTA. Females also preferred to use agreement strategies to respond to compliment offered by female than compliment offered by male. Compliment responses strategies are discussed in terms of gender. It can be concluded that the linguistic manipulations of compliment responses shown in this study indicate that no one strategy of compliment responses would work because different genders have different sets of strategies, thereby preventing any valid generalization. The current study offered important differences in using compliment responses between genders.